COVID-19 Outbreak and Financial Performance of Chinese Listed Firms: Evidence From Corporate Culture and Corporate Social Responsibility - Sun, Yunpeng; Li, Ying (Frontiers in Public Health, 2021)
This research described Chinese listed firms' COVID-19 Outbreak and financial performance using corporate culture (CC) and corporate social responsibility (CSR) evidence. The epidemic's impact on Chinese companies' profits was much less than the impact on their sales growth rates. Although the COVID-19 has had a more significant negative impact on the financial performance of Chinese listed companies in sectors that are more severely impacted, such as travel and entertainment, we believe that the financial performance of the medical industry has improved as a result of the outbreak. Meanwhile, Chinese listed companies in high-risk areas experience more significant financial losses during the epidemic, and the Hubei impact is hefty weight. Corporate social responsibility moderated the inverse relationship between this epidemic and Chinese firms' economic success. This research enhances the current literature on the effects of the COVID-19 on financial success and practical, realistic, and theoretical consequences in companies worldwide.